2019
DOI: 10.1136/bmjopen-2019-034323
|View full text |Cite
|
Sign up to set email alerts
|

Providing care to refugees through mainstream general practice in the southern health region of New Zealand: a qualitative study of primary healthcare professionals’ perspectives

Abstract: ObjectiveTo explore the perspectives of primary healthcare (PHC) professionals providing care to refugees through mainstream general practice.DesignQualitative exploratory design with semistructured interviews subjected to inductive thematic analysis.Setting and participantsNine general practices enrolled in the Dunedin Refugee Resettlement Programme, in New Zealand (NZ)’s southern health region. Participants included nine general practitioners and six practice nurses.ResultsThree analytical constructs were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 47 publications
(71 reference statements)
1
32
0
2
Order By: Relevance
“…This study examined GPs’ perceptions of the factors that challenge and support the treatment of refugees in regional general practice. These centred around culture, language and resource provision, which is consistent with much of refugee healthcare literature 10 19 21–25. Nonetheless, these data provide novel insights into how these factors are compounded by regional resettlement.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This study examined GPs’ perceptions of the factors that challenge and support the treatment of refugees in regional general practice. These centred around culture, language and resource provision, which is consistent with much of refugee healthcare literature 10 19 21–25. Nonetheless, these data provide novel insights into how these factors are compounded by regional resettlement.…”
Section: Discussionsupporting
confidence: 72%
“…Despite this, there has been limited study of clinicians’ experiences managing refugees’ needs in regional general practice. Those that have, have found that the ability to communicate effectively via interpreter services,21 22 limited local workforce capacity and refugees’ health literacy23 24 are key challenges to managing these patients who often have complex presentations that require longer consultations, which, in some instances, clinicians are not sufficiently remunerated for 19 20 25. Consistent with these barriers, additional clinical supports including access to interpreters, funded practice nurses and cultural training11 18 as well as the altruism of clinicians and local volunteers23 have each been found to support the management of refugees in general practice.…”
Section: Introductionmentioning
confidence: 99%
“… 50 , 51 In New Zealand, although childhood vaccines are freely available, navigating an unfamiliar health care system can hinder refugees’ ability to access and utilize publicly available health care services. 52 , 53 Moreover, at an organizational and structural level, literature has called for additional support for general practices and providers to improve immunization timeliness. 54 , 55 These supports will be particularly important to improve services for refugees as providers have noted substantial barriers to vaccinating people with refugee backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Kang, Tomkow dan Farrington (2019) dalam kajian mereka pula mendapati terdapat orang pelarian di UK yang tidak dilayan atau diberi layanan yang buruk oleh staf sokongan kesihatan semasa mendaftar di pusat perubatan kerana status mereka sebagai imigran, serta kaum dan agama mereka. Keempat, kekurangan sumber turut menjadi halangan untuk mendapat akses kepada penjagaan kesihatan (Kiselev et al, 2020;Richard et al, 2019;Robertshaw, Dhesi & Jones, 2017). Di samping kemudahan atau fasiliti, kekurangan sumber dalam penjagaan kesihatan termasuklah kekurangan doktor dan kakitangan sokongan kesihatan, serta jurubahasa (Kiselev et al, 2020;Robertshaw, Dhesi & Jones, 2017).…”
Section: Penjagaan Kesihatanunclassified
“…Selain itu, kekurangan tenaga kerja dalam sektor penjagaan kesihatan secara tidak langsung menambah beban kerja dan memberi tekanan tambahan buat petugas kesihatan untuk menyediakan khidmat penjagaan kesihatan kepada orang pelarian dan pencari suaka (Robertshaw, Dhesi & Jones, 2017). Sebagai contoh, kajian Richard et al (2019) mendapati kurangya sumber menyebabkan tempoh menunggu yang lama untuk rawatan kesihatan. Hal ini menyebabkan orang pelarian di New Zealand tidak mendapat akses kepada rawatan pada waktu yang diperlukan.…”
Section: Penjagaan Kesihatanunclassified